Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins - Jiang-Song Zhai; Da-Ming Du (Beilstein Journal of Organic Chemistry, 2022)
Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins have been developed to afford chiral dispiro[indene-pyrrolidine-pyrimidine]s. Through this strategy, the target products could be obtained in good to excellent yields with excellent stereoselectivities. In addition, the synthetic utility was verified through a gram-scale synthesis, one-pot three-component reactions and further transformation experiments of the products.